Light‐controllable polymeric material based on temperature‐sensitive hydrogels with incorporated graphene oxide (Phys. Status Solidi A 6∕2015). Issue 6 (June 2015) - Breuer, L.; Raue, M.; Kirschbaum, M.; Mang, T.; Schöning, M. J.; Thoelen, R.; Wagner, T.
<x xml:space="preserve">Abstract</x> A new method to locally address and stimulate hydrogel‐based actuators in microfluidic channels with the help of a focused light source is presented by Breuer et al. (pp. 1368–1374). To create light‐stimulated actuators, poly(N‐isopropylacrylamide) (PNIPAAm) hydrogel films were modified by incorporation of graphene oxide (GO). For this, GO dispersions were synthesized and characterized towards their optical properties and photothermal energy conversion. In addition, the influence of GO within the hydrogel network on the lower critical solution temperature (LCST) was investigated by differential scanning calorimetry (DSC). The optical absorbance and the response to illumination with a light source were determined as a function of the GO concentration for thin hydrogel films. The results underline that a focused light beam can easily heat hydrogels modified with GO above their LCST. Thus, the new method avoids the need for heater or other supplementary structures as used in conventional hydrogel‐based actutators for microfluidic set‐ups. Therefore, this work provides a promising concept to create miniaturized externally addressable actuators in the future.